ANALYSIS OF INTERACTIONAL AND TRANSACTIONAL LANGUAGE USED BY THE ENGLISH LECTURERS IN LEARNING PROCESS AT ENGLISH DEPARTMENT OF FKIP UKI TORAJA - Siumarlata, Viktor (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2014)
The objective of this research is to find out which is more dominant language used by the English lecturers in the learning process at English Department of FKIP UKI Toraja interactional or transactional, and in what situation interactional and transactional language used by the English lecturers in the learning process at English department of FKIP UKI Toraja. Descriptive qualitative and quantitative design is applied in this research to analyze the data. The data was analyzed was the script from the result of recording video in the learning process at English Department of FKIP UKI Toraja.The data was analyzed based on every utterance of lecturer in the learning process. The writer used snow ball method in choosing the sample of this research. The writer only took 5 lecturers as the sample from the total population was 21 lecturers.From the data analysis, the writer found that transactional language more dominant used by the English lecturers in the learning process. The result of this research shows that most of the lecturers used Transactional language in learning process then interactional. There are 1.194 utterances of the transactional language used by the lecturers in the learning process from the total number of utterances is 1.329. the transactional language used in a situation like greets student at beginning of the class, explain the topic, answer and giving the question and when lecturer gives example for the students. After conducting this study, it is expected to give the valuable contribution to the all lecturers in the learning process and can be more variation in using language. This research also is expected as additional knowledge and information for all people especially to the students that interested in conducting the similar study.  The writer does hope as language user: reader, writer, and whoever that want to study more about interactional and transactional language can be more improved.